2017
DOI: 10.1186/s12885-017-3609-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of PIVKA-II in the detection of hepatocellular carcinoma based on real-world clinical data

Abstract: BackgroundProtein Induced by Vitamin K Absence or Antagonist-II (PIVKA-II) is an efficient biomarker specific for hepatocellular carcinoma (HCC). Some researchers have proved that levels of PIVKA-II reflect HCC oncogenesis and progression. However, the effectiveness of PIVKA-II based on real-world clnical data has barely been studied.MethodsA total of 14,861 samples were tested in Southwest Hospital in over 2 years’ time. Among them, 4073 samples were PIVKA-II positive. Finally, a total of 2070 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 35 publications
3
63
0
2
Order By: Relevance
“…As the combination of PIVKA-II and AFP may increase sensitivity without decreasing specificity, the guidelines of the Japan Society of Hepatology recommended to measure these biomarkers during HCC surveillance (10). A recent study showed that the tumor markers might elevate at 0.5-1.5 years before the HCC lesion becomes obvious on diagnostic imaging (23). Furthermore, AFP and PIVKA-II elevation may suggest micrometastases, which may result in early recurrence within weeks or months after primary treatment (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…As the combination of PIVKA-II and AFP may increase sensitivity without decreasing specificity, the guidelines of the Japan Society of Hepatology recommended to measure these biomarkers during HCC surveillance (10). A recent study showed that the tumor markers might elevate at 0.5-1.5 years before the HCC lesion becomes obvious on diagnostic imaging (23). Furthermore, AFP and PIVKA-II elevation may suggest micrometastases, which may result in early recurrence within weeks or months after primary treatment (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…Des-gamma carboxyprothrombin may be used to assess not only the risk of HCC development but to predict its recurrence after surgical treatment. In the prospective study [107], application of DCP with AFP made it possible to suspect HCC 2 years before the diagnose verification. Further investigations are necessary in order to evaluate the effectiveness of this marker combination in the diagnosis of HCC [44].…”
Section: Reviewsmentioning
confidence: 99%
“…PIVKA-II is considered a suitable serum marker of HCC due to its high specificity. Thanks to the development of accurate measuring methods, Japanese Society Hepatology (JSH) recommends it as a marker of surveillance for HCC hepatitis, steatosis, benign nodules, liver abscess, pregnancy) [127]. Furthermore, an Italian observational cohort study in patients with US evidence of liver nodules, shows a higher specificity and positive predictive value (PPV) of PIVKA-II as compared to αFP; furthermore, the combined use of PIVKA-II and αFP improves the diagnostic accuracy as compared to either PIVKA-II or αFPalone (Table 1) [128].…”
Section: Surveillancementioning
confidence: 99%